2016
DOI: 10.1016/j.bjm.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Virulence genes and antimicrobial resistance of Pasteurella multocida isolated from poultry and swine

Abstract: Pasteurella multocida causes atrophic rhinitis in swine and fowl cholera in birds, and is a secondary agent in respiratory syndromes. Pathogenesis and virulence factors involved are still poorly understood. The aim of this study was to detect 22 virulence-associated genes by PCR, including capsular serogroups A, B and D genes and to evaluate the antimicrobial susceptibility of P. multocida strains from poultry and swine. ompH, oma87, plpB, psl, exbD-tonB, fur, hgbA, nanB, sodA, sodC, ptfA were detected in more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
38
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 36 publications
19
38
2
Order By: Relevance
“…The results showed that the capsular types of isolates were predominantly type A which is similar to that it was usual reported for P. multocida in China and other countries [34,35] . But we found one isolate of P. multocida was type F which is similar to the findings that reported previously [33] . Meanwhile, in these two provinces, antibiotic therapy is still an effective tool in the treatment of infections caused by P. multocida.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results showed that the capsular types of isolates were predominantly type A which is similar to that it was usual reported for P. multocida in China and other countries [34,35] . But we found one isolate of P. multocida was type F which is similar to the findings that reported previously [33] . Meanwhile, in these two provinces, antibiotic therapy is still an effective tool in the treatment of infections caused by P. multocida.…”
Section: Discussionsupporting
confidence: 92%
“…Parallel with the developments on the research of P. multocida, it has been almost completely controlled. Nevertheless, the pathogenic mechanism is currently not well understood, and thus it still restricts the development of livestock and poultry breeding and causes severe economic losses [9,33] . In this study, 23 strains of P. multocida isolated from poultry in Chongqing and Sichuan, China were tested for capsular antigens and antimicrobial susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To amplify the tadD gene, we used the PCR protocol described by Furian et al (2016). The amplification of the tadB, tadE and tadG genes was adapted from the protocol described by Moraes et al (2014).…”
mentioning
confidence: 99%